Визначення напрямів реалізації стратегії управління персоналом підприємства в контексті забезпечення її взаємозв’язку із конкурентною стратегією підприємства - Романюк, Л. М.; Харченко, І. В.; Romaniuk, L.; Kharchenko, I.; Харченко, И. В. (ЦНТУ, 2020)
У статті проаналізовано характерні ознаки класифікації конкурентних стратегій підприємства. Доведено важливість зв’язку конкурентної стратегії підприємства зі стратегією управління персоналом. Відповідно до конкурентних стратегій підприємства, визначено загальні вимоги до персоналу. Розроблено напрями реалізації стратегії управління персоналом. Визначено характерні ознаки напрямів реалізації стратегії управління персоналом для промислових підприємств. The purpose of the article is to identify and substantiate the implementation of human resource management strategy in accordance with the competitive strategy of an enterprise and to develop its characteristics. The analysis of the essence of a company's competitive strategies has been made: cost leadership, differentiation, optimal costs, targeted strategy of low costs and differentiation as well as requirements for qualification and assessment of personnel that are determined in accordance with these strategies. The competitive strategy of the enterprise determines the human resources management strategy, which should ensure the achievement of competitive strategy. The corresponding human resources management strategy is carried out by realization of following objectives: recruitment and selection of personnel, development and enhancement of skills and competences, determining the required level of expertise, development of personal qualities, ensuring the adaptation of personnel, further training, maintaining the necessary motivation of personnel and establishment of corporate culture.
Definition of the Guidelines for Implementation of the Human Resourcemanagement STrategy in the Context of Ensuring Its Correlation with the Competitive Strategy of the Enterprise
Определение направлений реализации стратегии управления персоналом предприятия в контексте обеспечения её взаимосвязи с конкурентной стратегией предприятия
Keywords: стратегія; персонал; підприємство; управлiння; конкурентна стратегія; strategy; human resources; enterprise; management; competitive strategy; стратегия; персонал; предприятие; управление; конкурентная стратегия